Burner stabilized flames: Towards reliable experiments and modelling of transient combustion. (15th January 2023) - Moroshkina, A.; Mislavskii, V.; Kichatov, B.; Gubernov, V.; Bykov, V.; Maas, U.
Abstract: In this work the diffusive–thermal pulsations of the burner stabilized methane-air flames are investigated experimentally, by analysing the OH ∗ chemiluminescence signal, and numerically within the model with various detailed reaction mechanisms. The employment of the nitrogen co-flow configuration to isolate the flame from the surrounding air allows us to obtain the experimental data of high fidelity such that the difference between the numerical data calculated with different reaction mechanisms is greater then the experimental uncertainty, demonstrating that the proposed technique can be used to verify the reaction mechanisms. Sensitivity analyses are carried out and it is shown that the steady and pulsating regimes of combustion has different although partly overlapping subsets of most important elementary reactions, especially for the case of relaxational oscillations in which the combustion front exhibits stages close to quenching and re-ignition. The suggested configuration can thus be used to access "transient combustion" and to gain an additional information to verify mechanisms. Highlights: Pulsations of CH 4 burner stabilized flames are investigated. The characteristics of pulsations are measured and calculated. It is proposed to use the unsteady flames to verify reaction kinetics. Sensitivity analysis is conducted for both steady and pulsating flames. The key elementary reactions are identified to update the reaction mechanisms.